2022
DOI: 10.1016/j.pacs.2021.100308
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning enables ultraviolet photoacoustic microscopy based histological imaging with near real-time virtual staining

Abstract: Histological images can reveal rich cellular information of tissue sections, which are widely used by pathologists in disease diagnosis. However, the gold standard for histopathological examination is based on thin sections on slides, which involves inevitable time-consuming and labor-intensive tissue processing steps, hindering the possibility of intraoperative pathological assessment of the precious patient specimens. Here, by incorporating ultraviolet photoacoustic microscopy (UV-PAM) with deep learning, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Sample preprocessing workflows are important for DL models [129]. Formalin-fixed, paraffin-embedded (FFPE) sections are the most common tissue samples in histopathology, resulting in high-quality images that may take days to be prepared, while frozen sections are the tissue samples that are obtained in urgent situations for a rapid overview of the tumor, providing images within less than an hour, albeit being more prone to the artifacts and disturbances in morphology [130,131]. Most DL studies use FFPE sections [81], but some studies have demonstrated good performance on frozen sections [37].…”
Section: Quality Control and Preprocessing Protocolsmentioning
confidence: 99%
“…Sample preprocessing workflows are important for DL models [129]. Formalin-fixed, paraffin-embedded (FFPE) sections are the most common tissue samples in histopathology, resulting in high-quality images that may take days to be prepared, while frozen sections are the tissue samples that are obtained in urgent situations for a rapid overview of the tumor, providing images within less than an hour, albeit being more prone to the artifacts and disturbances in morphology [130,131]. Most DL studies use FFPE sections [81], but some studies have demonstrated good performance on frozen sections [37].…”
Section: Quality Control and Preprocessing Protocolsmentioning
confidence: 99%
“…Developing these stained FFPE specimens for brightfield microscopic assessment relies on a laborious process of fixation, embedding, sectioning, and staining 3 , a procedure which takes several days to complete 4 . This lengthy process has motivated the adoption of frozen section (FS) histology, a technique which is commonly used for rapid intraoperative assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to virtually stain microscopic images of unlabeled tissue sections was demonstrated through deep neural networks, avoiding the laborious and time-consuming histochemical staining processes. These deep learning-based label-free virtual staining methods can use different input imaging modalities, such as autofluorescence microscopy [2][3][4], hyperspectral imaging [5], quantitative phase imaging (QPI) [6], reflectance confocal microscopy [7], and photoacoustic microscopy [8], among others [9][10][11]. Virtual staining, in general, has the potential to be used as a substitute for histochemical staining, providing savings in both costs and tissue processing time.…”
Section: Introductionmentioning
confidence: 99%